Interstitial pneumonia in feedyard cattle: risk factors and diagnosis - Schmidt, Paige Hildegarde (My University, 2024)
Interstitial pneumonia is an economically important disease in feedyard cattle due to higher incidence in cattle late in the feeding period. Understanding previous research on interstitial pneumonia and refining the field case definition are important to improve knowledge for this disease syndrome, and determining risk factors for interstitial pneumonia early in the feeding period can assist in predicting affected cattle. A systematic review was utilized with the objective to describe the clinical signs, etiologies, risk factors, pathologies, and treatments of feedyard AIP. The relevant literature was identified using three databases: PubMed, CABI Direct Library, and AGRICOLA with criteria to include only primary literature that took place in North American feedyard cattle. The original search resulted in 807 publications. A systematic screening process was utilized that identified 19 articles that fit the inclusion criteria. Six articles described clinical signs used to diagnose AIP and the most common were severe respiratory distress, increased expiratory effort and grunting when breathing. Eleven articles evaluated various etiologies which included bovine respiratory syncytial virus (BRSV), other infectious pathogens, melengestrol acetate (MGA) and 3-methylindole (3-MI). The most frequently evaluated aspect of AIP was pathology, with 17 articles providing detailed descriptions of AIP pathological and diagnostic features. Frequently used gross pathological characteristics included intralobular emphysema or edema, a “checkerboard” appearance, and diffuse, overinflated lung lobes. The most frequent histopathological features recognized were hyaline membranes, type II pneumocyte hyperplasia and bronchiolitis (fibrosa) obliterans. Eleven publications evaluated various risk factors that may contribute to AIP. Common risk factors analyzed included season, sex, days on feed (DOF) at onset and DOF at death. No primary literature was identified evaluating AIP treatments, however, one article assessed feather meal and vitamin E supplementation as a preventative for AIP. The literature review identified several knowledge gaps related to AIP in feedyard cattle and the areas where there is limited published research. The objective of the second study was to utilize gross necropsy and histopathology to determine the frequency of bronchopneumonia (BP), acute interstitial pneumonia (AIP), and bronchopneumonia with an interstitial pneumonia (BIP) and the agreement between gross and histopathological diagnosis. Gross necropsies were performed on 417 feedyard cattle, across six Kansas feedyards in a cross-sectional, observational study. The frequency of each pulmonary diagnosis was determined with descriptive statistics for both methodologies. Generalized linear mixed models were used to evaluate the agreement between histopathological and gross diagnosis. Both diagnostic modalities identified BP and BIP as the most common pulmonary syndromes. Bronchopneumonia was identified in 36.6% of mortalities followed by BIP in 35.8% of mortalities and AIP in 10.0% of mortalities. The histopathological diagnosis revealed 32.3% of lungs had BP, 36.0% of lungs had BIP and 12.2% of lungs had AIP. Histopathological diagnosis tended (P-value = 0.06) to be associated with gross diagnosis. Four lung samples were acquired from right cranioventral, left cranioventral, right caudodorsal, and left caudodorsal to determine agreement in histopathological diagnosis. Lung sample location was not significantly associated with the probability of agreement between the overall histopathological diagnosis and each sample diagnosis. Refined mortality diagnostics are necessary to improve understanding of pulmonary pathology in feedyard cattle, which can be valuable for evaluating and adjusting therapeutic interventions. The objective of the third study was to determine the probability of at least one AIP mortality occurring in a cohort (AIPMort) and potential associations with cohort arrival characteristics and disease incidence in the first 45 days on feed. A retrospective data analysis was performed using 27,324 cohorts from 20 U.S. commercial feedyards, over a 4-year time span. At least one AIP mortality was present in 5,525 (20.2%) cohorts. The risk factors analyzed included cohort sex, head received, arrival weight, arrival month, BRD morbidity (BRDMorb45), BRD mortality (BRDMort45), digestive morbidity (DigestMorb45) and digestive mortality (DigestMort45). All risk factors were significantly associated with AIPMort. Heifer cohorts were more likely to (19.5% ± 0.048) experience AIPMort than steer cohorts (13.3% ± 0.035). Cohorts that experienced high BRD morbidity (>5%) and mortality (>0.1%) in the first 45 days on feed were associated with higher AIPMort compared to cohorts with less BRD challenge. Further research is still necessary to assess the etiology of this disease, and the individual cattle affected. However, this cohort data guides further research to the specific risk factors of cattle that experience AIP mortalities. Interstitial pneumonia in feedyard cattle, although rare at the individual animal level continues to have significant negative economic and cattle welfare impacts. Bronchopneumonia with an interstitial pneumonia has been documented for many years but not consistently acknowledged as a separate disease process. Further research is necessary to investigate these two pulmonary diseases, their pathogenesis and the cattle affected in the feedyard setting.
Keywords: Interstitial pneumonia; Feedlot; Cattle; Necropsy; Bovine respiratory disease